Similarity analysis, synthesis, and bioassay of antibacterial cyclic peptidomimetics - Berhanu, Workalemahu M.; Ibrahim, Mohamed A.; Pillai, Girinath G.; Oliferenko, Alexander A.; Khelashvili, Levan; Jabeen, Farukh; Mirza, Bushra; Ansari, Farzana Latif; ul-Haq, Ihsan; El-Feky, Said A.; Katritzky, Alan R. (Beilstein Journal of Organic Chemistry, 2012)
The chemical similarity of antibacterial cyclic peptides and peptidomimetics was studied in order to identify new promising cyclic scaffolds. A large descriptor space coupled with cluster analysis was employed to digitize known antibacterial structures and to gauge the potential of new peptidomimetic macrocycles, which were conveniently synthesized by acylbenzotriazole methodology. Some of the synthesized compounds were tested against an array of microorganisms and showed antibacterial activity against Bordetella bronchistepica, Micrococcus luteus, and Salmonella typhimurium.
Keywords: antibacterial; cluster analysis; N-acylbenzotriazoles; peptidomimetics; similarity

(untitled) - Powers, J.-P. S.; Hancock, R. E. W. (Peptides, 2003)

(untitled) - Dartois, V.; Sanchez-Quesada, J.; Cabezas, E.; Chi, E.; Dubbelde, C.; Dunn, C.; Granja, J.; Gritzen, C.; Weinberger, D.; Ghadiri, M. R.; Parr, T. R., Jr (Antimicrob. Agents Chemother., 2005)

(untitled) - Epand, R. M.; Vogel, H. J. (Biochim. Biophys. Acta, 1999)

(untitled) - Singh, A.; Wilczynski, A.; Holder, J. R.; Witek, R. M.; Dirain, M. L.; Xiang, Z.; Edison, A. S.; Haskell-Luevano, C. (J. Med. Chem., 2011)

(untitled) - Bach, A.; Strømgaard, K. (Synthesis, 2011)

(untitled) - Biron, E.; Chatterjee, J.; Kessler, H. (Org. Lett., 2006)

(untitled) - Tornøe, C. W.; Sanderson, S. J.; Mottram, J. C.; Coombs, G. H.; Meldal, M. (J. Comb. Chem., 2004)

(untitled) - Saitton, S.; Kihlberg, J.; Luthman, K. (Tetrahedron, 2004)

(untitled) - McComsey, D. F.; Hawkins, M. J.; Andrade-Gordon, P.; Addo, M. F.; Oksenberg, D.; Maryanoff, B. E. (Bioorg. Med. Chem. Lett., 1999)

(untitled) - Pedersen, D. S.; Abell, A. (Eur. J. Org. Chem., 2011)

(untitled) - Appendino, G.; Bacchiega, S.; Minassi, A.; Cascio, M. G.; De Petrocellis, L.; Di Marzo, V. D. (Angew. Chem., Int. Ed., 2007)

(untitled) - Tam, A.; Arnold, U.; Soellner, M. B.; Raines, R. T. (J. Am. Chem. Soc., 2007)

(untitled) - Brik, A.; Yang, Y.-Y.; Ficht, S.; Wang, C.-H. (J. Am. Chem. Soc., 2006)

(untitled) - Borg, S.; Vollinga, R. C.; Labarre, M.; Payza, K.; Terenius, L.; Luthman, K. (J. Med. Chem., 1999)

(untitled) - Balzarini, J.; Stevens, M.; De Clercq, E.; Schols, D.; Pannecouque, C. (J. Antimicrob. Chemother., 2005)

(untitled) - Haviv, F.; DeNet, R. W.; Michaels, R. J.; Ratajczyk, J. D.; Carter, G. W.; Young, P. R. (J. Med. Chem., 1983)

(untitled) - Thirumurugan, P.; Mahalaxmi, S.; Perumal, P. T. (J. Chem. Sci., 2010)

(untitled) - Phillips, O. A.; Knaus, E. E. (Drug Des. Delivery, 1991)

(untitled) - Reck, F.; Zhou, F.; Eyermann, C. J.; Kem, G.; Carcanague, D.; Ioannidis, G.; Illingworth, R.; Poon, G.; Gravestock, M. B. (J. Med. Chem., 2007)

(untitled) - Liu, M. C.; Lin, T. C.; Sartorelli, A. C. (J. Med. Chem., 1992)

(untitled) - Kim, G.-J.; Park, D.-W.; Tak, Y.-S. (Catal. Lett., 2000)

(untitled) - Li, Z.; Jablonski, C. (Chem. Commun., 1999)

(untitled) - Kubik, S. (Chem. Soc. Rev., 2009)

(untitled) - Ranganathan, D.; Thomas, A.; Haridas, V.; Kurur, S.; Madhusudanan, K. P.; Roy, R.; Kunwar, A. C.; Sarma, A. V. S.; Vairamani, M.; Sarma, K. D. (J. Org. Chem., 1999)

(untitled) - Ranganathan, D.; Haridas, V.; Gilardi, R.; Karle, I. L. (J. Am. Chem. Soc., 1998)

(untitled) - Pintér, Á.; Haberhauer, G. (Tetrahedron, 2009)

(untitled) - Montero, A.; Albericio, F.; Royo, M.; Herradon, B. (Eur. J. Org. Chem., 2007)

(untitled) - Wang, X.; Wang, Q.; Huang, X.; Wang, T.; Yu, X. (ARKIVOC, 2006)

(untitled) - Hancock, R. E. W. (Lancet Infect. Dis., 2001)

(untitled) - Wu, M. H.; Hancock, R. E. W. (Antimicrob. Agents Chemother., 1999)

(untitled) - Fales-Williams, A. J.; Gallup, J. M.; Ramirez-Romero, R.; Brogden, K. A.; Ackermann, M. R. (Clin. Diagn. Lab. Immunol., 2002)

Generalized Method of Moments - Alastair, A. R. (Oxford University Press, 2005)

(untitled) - Bender, A.; Glen, R. C. (Org. Biomol. Chem., 2004)

(untitled) - Katritzky, A. R.; Khelashvili, L.; Mohapatra, P. P.; Steel, P. J. (Synthesis, 2007)

(untitled) - Katritzky, A. R.; Angrish, P.; Todadze, E. (Synlett, 2009)

(untitled) - Katritzky, A. R.; Tala, S. R.; Abo-Dya, N. E.; Gyanda, K.; El-Gendy, B. E.-D. M.; Abdel-Samii, Z. K.; Steel, P. J. (J. Org. Chem., 2009)

CODESSA Pro (University of Florida, 2001)

(untitled) - von Nussbaum, F. V.; Anlauf, S.; Freiberg, C.; Benet-Buchholz, J.; Schamberger, J.; Henkel, T.; Schiffer, G.; Häbich, D. (ChemMedChem, 2008)

(untitled) - Morel, A. F.; Maldaner, G.; Ilha, V.; Missau, F.; da Silva, U. F.; Dalcol, I. I. (Phytochemistry, 2005)

(untitled) - Morel, A. F.; Araujo, C. A.; da Silva, U. F.; Hoelzel, S. C. S. M.; Záchia, R.; Bastos, N. R. (Phytochemistry, 2002)

(untitled) - Giacomelli, S. R.; Maldaner, G.; Gonzaga, W. A.; Garcia, C. M.; da Silva, U. F.; Dalcol, I. I.; Morel, A. F. (Phytochemistry, 2004)

(untitled) - Socha, A. M.; Tan, N. Y.; LaPlante, K. L.; Sello, J. K. (Bioorg. Med. Chem., 2010)

(untitled) - von Nussbaum, F.; Brands, M.; Hinzen, B.; Weigand, S.; Häbich, D. (Angew. Chem., Int. Ed., 2006)

(untitled) - Linde, R. G., II; Birsner, N. C.; Chandrasekaran, R. Y.; Clancy, J.; Howe, R. J.; Lyssikatos, J. P.; MacLelland, C. P.; Magee, T. V.; Petitpas, J. W.; Rainville, J. P.; Su, W.-G.; Vu, C. B.; et al. (Bioorg. Med. Chem. Lett., 1997)

(untitled) - Norcia, L. J. L.; Silvia, A. M.; Dirlam, J. P.; Schnur, R. C.; Bergeron, J. M.; Retsema, J. A.; Hayashi, S. F. (J. Antibiot., 1999)

(untitled) - Lyssikatos, J. P.; Chang, S.-P.; Clancy, J.; Dirlam, J. P.; Finegan, S. M.; Girard, A. E.; Hayashi, S. F.; Larson, D. P.; Lee, A. S.; Linde, R. G., II; MacLelland, C. P.; Petipas, J. W.; et al. (Bioorg. Med. Chem. Lett., 1997)

(untitled) - Dirlam, J. P.; Belton, A. M.; Birsner, N. C.; Brooks, R. R.; Chang, S.-P.; Chandrasekaran, R. Y.; Clancy, J.; Cronin, B. J.; Dirlam, B. P.; Finegan, S. M.; Froshauer, S. A.; Girard, A. E.; et al. (Bioorg. Med. Chem. Lett., 1997)

(untitled) - Holliday, J. D.; Rodgers, S. L.; Willett, P.; Chen, M. Y.; Mahfouf, M.; Lawson, K. (J. Chem. Inf. Comput. Sci., 2004)

(untitled) - Stahl, M.; Mauser, H.; Tsui, M.; Taylor, N. R. (J. Med. Chem., 2005)

(untitled) - Adamson, G. W.; Bawden, D. (J. Chem. Inf. Comput. Sci., 1981)

Instant JChem 5.5.0; Marvin 5.6.0 (ChemAxon Kft., 2011)

(untitled) - Allinger, N. L. (J. Am. Chem. Soc., 1977)

ChemBioDraw Ultra, Version 12.0.2 (Cambridgesoft, 2010)

(untitled) - Dewar, M. J. S.; Zoebisch, E. G.; Healy, E. F.; Stewart, J. J. P. (J. Am. Chem. Soc., 1985)

Molecular Descriptors in QSAR/QSPR - Karelson, M. (Wiley Interscience, 2000)

(untitled) - Katritzky, A. R.; Kuanar, M.; Slavov, S.; Hall, C. D.; Karelson, M.; Kahn, I.; Dobchev, D. A. (Chem. Rev., 2010)

STATISTICA, Version 6 (StatSoft, Inc., 2001)